Morphological and functional diversity of spatially resolved vestibular ganglion neuron cell types - Ruiqi Liu; Jingyue Liu; Zhiyu Chen; Jingying Li; Zhiyong Liu; Shuohao Sun (Proceedings of the National Academy of Sciences, 2026)
Vestibular ganglion neurons (VGNs) are the primary sensory neurons of the vestibular system, a relatively understudied sensory modality that is essential for maintaining visual stability and postural balance. Compared with other sensory systems, our understanding of the molecular heterogeneity of VGNs and its contribution to the diverse functions of the vestibular system remains limited. Using single-cell and spatial transcriptomics, we defined five transcriptionally distinct VGN cell types with discrete spatial distributions across the ganglion. These VGN cell types demonstrate organ-specific innervation patterns, target defined zones within each organ, and form characteristic synaptic endings. To probe their functional roles, we generated genetic tools that selectively label each VGN cell type. Leveraging these tools, we identified a cell type contributing to gravity sensing and otolith-dependent vestibulo-ocular reflexes, revealing a cell type–specific basis for modality-selective vestibular computations.